2010
DOI: 10.1366/000370210792081028
|View full text |Cite
|
Sign up to set email alerts
|

A Prototype Hand-Held Raman Sensor for the in situ Characterization of Meat Quality

Abstract: As a tool for the in situ characterization of meat quality, a hand-held Raman sensor head using an excitation wavelength of 671 nm was developed. A microsystem-based external cavity diode laser module was integrated into the sensor head and attached to a Raman probe, which is equipped with lens optics for excitation and signal collection as well as a Raman filter stage for Rayleigh rejection. The Raman signal was guided by an optical fiber to the detection unit, which was in the initial phase a laboratory spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 18 publications
(21 reference statements)
0
29
0
3
Order By: Relevance
“…A hand held RS device with a 671 nm laser (Schmidt, Sowoidnich, & Kronfeldt, 2010) (Fig. 1.) that had been calibrated using the spectra of polystyrene, was used for measurement.…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…A hand held RS device with a 671 nm laser (Schmidt, Sowoidnich, & Kronfeldt, 2010) (Fig. 1.) that had been calibrated using the spectra of polystyrene, was used for measurement.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…This was established using the hand held Raman device that had previously been developed to assess the quality of pork (Schmidt et al, 2009). The process uses PCA to identify lipid contributions to the spectra by comparing key vibrations in each spectrum with saved components (Scheier, 2014;Schmidt et al, 2010). As pork subcutaneous adipose tissue is higher in long chain PUFAs in comparison to lamb (Wood et al, 2008) and RS is sensitive to species differences in FA composition (Beattie et al, 2007), it is hypothesised that this process of separating protein and lipid spectra may have reduced the ability to predict major FA composition.…”
Section: Prediction Of Imf and The Major Fa Groupsmentioning
confidence: 99%
“…1 (Schmidt et al, 2010). Briefly, the 671 nm emission of a microsystem diode laser (Ferdinand-Braun Institute, Berlin, Germany) was focused on the sample by means of an in-house manufactured Raman probe which collected the backscattered radiation and provided the rejection of the elastically scattered light.…”
Section: Measurementsmentioning
confidence: 99%
“…Such a device has recently been developed based on a laser diode emitting light at 671 nm (Schmidt, Sowoidnich, Maiwald, Sumpf, & Kronfeldt, 2009). Compared to the more convenient 785 nm excitation the shorter laser wavelength allows for faster measurements by a factor of 2 Meat Science 93 (2013) 138-143 due to higher scattering intensities according to the λ −4 law and due to an increased sensitivity of CCD detectors (Schmidt, Sowoidnich, & Kronfeldt, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to NIR spectroscopy, water is not a challenge during Raman measurements as water is a very weak Raman scatter. Moreover, handheld Raman spectroscopy is already developed and has been used to study meat spoilage (Sowoidnich, Schmidt, Kronfeldt, & Schw€ agele, 2012) and other meat quality parameters (Schmidt, Sowoidnich, & Kronfeldt, 2010;Schmidt, Scheier, & Hopkins, 2013). Recent results have shown that Raman spectroscopy can be used to predict EPT and time of cooked meat (Berhe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%